Efektivitas Penggunaan Bahan Ajar Flipbook dengan Platform Google Classroom dalam Pembelajaran Jarak Jauh - Ai Tin Sumartini (Jurnal Didaktika Pendidikan Dasar, 2022)
The occurrence of the Covid-19 pandemic that lasted more than a year had a tremendous influence in the learning process, so distance learning must be done. Various problems that arise in the implementation of PJJ, efforts are needed to overcome it. The purpose of this study is to find out the effectiveness of the use of flipbook teaching materials with the google classroom platform in distance learning in the dynamics material of Pancasila realization. The research method used is a descriptive method, which describes the implementation of distance learning with the use of flipbook teaching materials. Flipbook teaching materials embedded in the google classroom platform as LMS (Learning Management System) have an attractive look, easy to use, easy to understand subject matter, contains clear text and images displayed supporting the understanding of the subject matter. The excess use of flipbook teaching materials based on the results of the questionnaire shows the predicate of good judgment, as well as the level of understanding of learners of the subject matter obtained an average value above KKM.